2015
DOI: 10.1016/j.chom.2014.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin-Induced Hypoferremia Is a Critical Host Defense Mechanism against the Siderophilic Bacterium Vibrio vulnificus

Abstract: SUMMARY Hereditary hemochromatosis, an iron overload disease caused by a deficiency in the iron-regulatory hormone hepcidin, is associated with lethal infections by siderophilic bacteria. To elucidate the mechanisms of this susceptibility, we infected wild-type and hepcidin-deficient mice with the siderophilic bacterium Vibrio vulnificus, and found that hepcidin deficiency results in increased bacteremia and decreased survival of infected mice, which can be partially ameliorated by dietary iron depletion. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
186
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(194 citation statements)
references
References 47 publications
(55 reference statements)
4
186
0
4
Order By: Relevance
“…In contrast, the mRNA levels of hepcidin, a peptide hormone that regulates iron levels by degrading FPN, shows only moderate elevation at 24 h postinfection. Previous studies with infection models have shown hepcidin induction occurring during the first 12 h of infection (64), and the moderate change we observe is after the time window at which the hepcidin transcripts increase. The notable decrease in FPN mRNA suggests that hepatic iron regulation at this time point may also involve additional hepcidin-independent pathways that involve transcriptional regulation of FPN (65,66).…”
Section: Icl-1 Visualizes Changes In Labile Iron Pools In An a Baumasupporting
confidence: 56%
“…In contrast, the mRNA levels of hepcidin, a peptide hormone that regulates iron levels by degrading FPN, shows only moderate elevation at 24 h postinfection. Previous studies with infection models have shown hepcidin induction occurring during the first 12 h of infection (64), and the moderate change we observe is after the time window at which the hepcidin transcripts increase. The notable decrease in FPN mRNA suggests that hepatic iron regulation at this time point may also involve additional hepcidin-independent pathways that involve transcriptional regulation of FPN (65,66).…”
Section: Icl-1 Visualizes Changes In Labile Iron Pools In An a Baumasupporting
confidence: 56%
“…19,20 Future investigations should also consider whether interindividual differences in hepcidin could manifest in differential susceptibility to other iron-requiring pathogens, such as Vibrio spp. 48 and HIV-1, or macrophagetropic pathogens, such as Mycobacterium tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking hepcidin show markedly decreased survival when infected with the siderophilic Vibrio vulnificus, and treatment with synthetic minihepcidins dramatically improves survival (54). The main mediator of increased hepcidin production during infection is IL-6 (55), which transcriptionally stimulates hepcidin synthesis via STAT3.…”
Section: Hepcidin a Component Of Innate Immunitymentioning
confidence: 99%